THE ECONOMIC IMPACT OF ESPORTS ON LOCAL ECONOMIES: A CASE STUDY ANALYSIS OF MAJOR EVENTS - Gupta, Heenal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Esports has grown into a global wonder, with millions of fans and players contributing and witnessing across the world. Esports dashes its roots to the 1970s and 1980s, with the escalation of arcade gaming and initial competitive gaming events. But with the decades with all the advances in internet connectivity, technology, and gaming culture contribution towards the growth and professionalization of esports is being seen.